Caregiver risk preferences for delaying loss of ambulation in Duchenne muscular dystrophy in the United States - Shafrin, Jason; Zawadzki, Nadine; Marin, Moises; Audhya, Ivana; Sedita, Lauren E.; Kulkarni, Natasha; Klimchak, Alexa C. (Current medical research and opinion, 2025)
Quantify caregiver risk preferences to inform the "value of hope" for Duchenne muscular dystrophy (DMD) therapies affecting time to loss of ambulation (LoA). Caregivers (medical decision-makers) of patients with DMD were surveyed to evaluate their preferences across 2 therapies with identical expected (average) time to LoA: 1 with variable (i.e. possibly longer or shorter than average) time to LoA and 1 with fixed (i.e. certain) time to LoA. Time to LoA with the fixed therapy was altered to determine the caregiver's indifference point. Study endpoints were (i) the share of caregivers who preferred the variable (vs fixed) time to LoA therapy; and (ii) the length of fixed time to LoA that would result in caregiver indifference between the variable and fixed therapies, calculated using parameter estimation by sequential testing. The base case examined therapy choice for a hypothetical ambulatory DMD patient aged 9 years; sensitivity analyses explored preferences for younger (aged 5) and older (aged 13) patients. Among 103 caregivers surveyed, 72 (69.9%) preferred the variable time to LoA therapy for a hypothetical 9-year-old patient with DMD ( < 0.001). Caregivers were willing to give up 11.5 months ( < 0.001) of certain time to LoA for a chance of longer time to LoA. Caregivers' preference for the variable therapy decreased with hypothetical patient age at treatment initiation, from 72.8% (75/103) for age 5 ( < 0.001) to 60.2% (62/103) for age 13 ( = 0.048). Caregivers of patients with DMD demonstrated risk tolerance (positive value of hope) for therapies that could delay LoA.